Entanglement between dependent degrees of freedom: Quasiparticle correlations - Barkhausen, Franziska; Ares Santos, Laura; Schumacher, Stefan; Sperling, Jan (Physical Review A)

Topological edge and corner states in coupled wave lattices in nonlinear polariton condensates - Schneider, Tobias; Gao, Wenlong; Zentgraf, Thomas; Schumacher, Stefan; Ma, Xuekai (Nanophotonics)
Abstract Topological states have been widely investigated in different types of systems and lattices. In the present work, we report on topological edge states in double-wave (DW) chains, which can be described by a generalized Aubry-André-Harper (AAH) model. For the specific system of a driven-dissipative exciton polariton system we show that in such potential chains, different types of edge states can form. For resonant optical excitation, we further find that the optical nonlinearity leads to a multistability of different edge states. This includes topologically protected edge states evolved directly from individual linear eigenstates as well as additional edge states that originate from nonlinearity-induced localization of bulk states. Extending the system into two dimensions (2D) by stacking horizontal DW chains in the vertical direction, we also create 2D multi-wave lattices. In such 2D lattices multiple Su–Schrieffer–Heeger (SSH) chains appear along the vertical direction. The combination of DW chains in the horizonal and SSH chains in the vertical direction then results in the formation of higher-order topological insulator corner states. Multistable corner states emerge in the nonlinear regime.

Manipulating spectral topology and exceptional points by nonlinearity in non-Hermitian polariton systems - Wingenbach, Jan; Schumacher, Stefan; Ma, Xuekai (Physical Review Research)
Exceptional points (EPs), with their intriguing spectral topology, have attracted considerable attention in a broad range of physical systems, with potential sensing applications driving much of the present research in this field. Here, we investigate spectral topology and EPs in systems with significant nonlinearity, exemplified by a nonequilibrium exciton-polariton condensate. With the possibility to control loss and gain and nonlinearity by optical means, this system allows for a comprehensive analysis of the interplay of nonlinearities (Kerr type and saturable gain) and non-Hermiticity. Not only do we find that EPs can be intentionally shifted in parameter space by the saturable gain, but we also observe intriguing rotations and intersections of Riemann surfaces and find nonlinearity-enhanced sensing capabilities. With this, our results illustrate the potential of tailoring spectral topology and related phenomena in non-Hermitian systems by nonlinearity. Published by the American Physical Society 2024

Room-Temperature Electrical Field-Enhanced Ultrafast Switch in Organic Microcavity Polariton Condensates - De, Jianbo; Ma, Xuekai; Yin, Fan; Ren, Jiahuan; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing; Malpuech, Guillaume; Solnyshkov, Dmitry (Journal of the American Chemical Society (JACS))
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Tilting nondispersive bands in an empty microcavity - Gao, Ying; Li, Yao; Ma, Xuekai; Gao, Meini; Dai, Haitao; Schumacher, Stefan; Gao, Tingge (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Switching Off a Microcavity Polariton Condensate near the Exceptional Point - Li, Yao; Ma, Xuekai; Hatzopoulos, Zaharias; Savvidis, Pavlos G.; Schumacher, Stefan; Gao, Tingge (ACS Photonics)

Helical Polariton Lasing from Topological Valleys in an Organic Crystalline Microcavity - Long, Teng; Ma, Xuekai; Ren, Jiahuan; Li, Feng; Liao, Qing; Schumacher, Stefan; Malpuech, Guillaume; Solnyshkov, Dmitry; Fu, Hongbing (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Manipulating polariton condensates by Rashba-Dresselhaus coupling at room temperature - Li, Yao; Ma, Xuekai; Zhai, Xiaokun; Gao, Meini; Dai, Haitao; Schumacher, Stefan; Gao, Tingge (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Unidirectional vortex waveguides and multistable vortex pairs in polariton condensates - Gao, Xinghui; Hu, Wei; Schumacher, Stefan; Ma, Xuekai (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Quantifying Quantum Coherence in Polariton Condensates - Lüders, Carolin; Pukrop, Matthias; Rozas, Elena; Schneider, Christian; Höfling, Sven; Sperling, Jan; Schumacher, Stefan; Aßmann, Marc (PRX Quantum)

Split-ring polariton condensates as macroscopic two-level quantum systems - Xue, Yan; Chestnov, Igor; Sedov, Evgeny; Kiktenko, Evgeniy; Fedorov, Aleksey K.; Schumacher, Stefan; Ma, Xuekai; Kavokin, Alexey (Physical Review Research)

Structuring coflowing and counterflowing currents of polariton condensates in concentric ring-shaped and elliptical potentials - Barkhausen, Franziska; Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

Formation dynamics of exciton-polariton vortices created by nonresonant annular pumping - Berger, Bernd; Schmidt, Daniel; Ma, Xuekai; Schumacher, Stefan; Schneider, Christian; Höfling, Sven; Assmann, Marc (Physical Review B)

Realization of all-optical vortex switching in exciton-polariton condensates - Ma, Xuekai; Berger, B; Aßmann, M; Driben, R; Meier, Torsten; Schneider, C; Höfling, S; Schumacher, Stefan (Nature Communications)

Efficient Bosonic Condensation of Exciton Polaritons in an H-Aggregate Organic Single-Crystal Microcavity. - Ren, J; Liao, Q; Huang, H; Li, Y; Gao, T; Ma, Xuekai; Schumacher, Stefan; Yao, J; Bai, S; Fu, H (Nano Letters)

Topological edge states of nonequilibrium polaritons in hollow honeycomb arrays. - Ma, Xuekai; Kartashov, YV; Ferrando, A; Schumacher, Stefan (Optics Letters)

Multistable circular currents of polariton condensates trapped in ring potentials. - Barkhausen, F; Schumacher, Stefan; Ma, Xuekai (Optics Letters)

Chiral condensates in a polariton hexagonal ring. - Ma, Xuekai; Kartashov, YV; Kavokin, A; Schumacher, Stefan (Optics Letters)

Circular polarization reversal of half-vortex cores in polariton condensates - Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

Spiraling vortices in exciton-polariton condensates - Ma, Xuekai; Kartashov, Yaroslav V.; Gao, Tingge; Torner, Lluis; Schumacher, Stefan (Physical Review B)